Nutritive Value, Digestibility, and Gas Production of Pennisetum purpureum Silage Supplemented with Saccharomyces cerevisiae and Lactobacillus plantarum - Riyanti, L.; Zahera, R.; Kisworo, A. N.; Wihansah, R. R. S.; Febriza, G. (Faculty of Animal Science, IPB University, 2024)
The purpose of this study was to evaluate the use of Saccharomyces cerevisiae and Lactobacillus plantarum as silage additives and their combinations on the physico-chemical and microbiological quality of Pennisetum purpureum cv. Mott silage and assess fermentation characteristics, digestibility, and in vitro gas production. The experiment used a completely randomized design with 4 treatments and 5 replications. The treatments are: T0= dwarf elephant grass silage + 3% molasses, T1= T0 + S. cerevisiae, T2= T0 + L. plantarum, and T3= T0 + S. cerevisiae + L. plantarum. Variables measured were organoleptic, physical, microbial, nutrient composition, in vitro fermentation characteristics and nutrient digestibility, as well as total gas and methane productions. The result showed that all silages had good physical quality, low pH (<3.8) and NH3 content, and high fleigh point. Inoculants decreased the percentage of dry matter, crude protein, ether extract (p<0.05), increased crude fiber, and decreased the composition of nitrogen-free extract and non-fiber carbohydrate (p<0.05) but it was able to increase Ca and P. Total gas production of T0 was the highest among treatments, while the T3 had the lowest total gas and methane productions (p<0.05). The supplementation of S. cerevisiae and L. plantarum as a silage improved organoleptic, physical, and microbiological qualities. Although the nutrient composition did not increase significantly, the combination of 2 (two) inoculants was able to improve fermentation activity in the rumen, increase total volatile fatty acid (VFA), dry matter and organic matter digestibility, reduce total gas production and the ratio of methane gas production to VFA.